2017
DOI: 10.1177/0015732516663318
|View full text |Cite
|
Sign up to set email alerts
|

Prospects of India–GCC Trade Relations

Abstract: India–Gulf Co-operation Council (GCC) countries trade relation has intensified in the last two decade. GCC is one of the largest trading partners of India. In this paper, an attempt has been made to explore India’s trade potential with GCC countries at HS-2 digit for the period 2001–2014. Various trade indices have been calculated to infer about mutual trade potential. The findings of this study reveal that India’s trade is more intense with GCC countries compared with its trading patterns with rest of the wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…The PBT estimation equation used by Mukherji (2005) was named Indicative Trading Potential by Helmers & Pasteels (2006). In addition, Bano et al (2013), Alam (2017), Taneja et al (2020) and Li and & Li (2020) used PBT for international trade potential analysis. The idea of PBT is to evaluate the supply-demand capabilities of the supplying countries under optimal conditions.…”
Section: Data Data Sources and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…The PBT estimation equation used by Mukherji (2005) was named Indicative Trading Potential by Helmers & Pasteels (2006). In addition, Bano et al (2013), Alam (2017), Taneja et al (2020) and Li and & Li (2020) used PBT for international trade potential analysis. The idea of PBT is to evaluate the supply-demand capabilities of the supplying countries under optimal conditions.…”
Section: Data Data Sources and Methodologymentioning
confidence: 99%
“…Kojima (1964) analysed the trade patterns of industrialised nations using the trade intensity index, which is divided into export intensity and import intensity. This trade intensity index is prevalent in trade analysis from the Kojima has developed index use (Alam, 2017; Marukawa, 2021; Raghurampatruni et al, 2021; Sawhney & Kiran, 2019). In Ricardo’s theory of comparative advantage, measurements are attainable if product-wise cost data is available for testing.…”
Section: Review Of Literaturementioning
confidence: 99%
“…However, the findings of the study also showed that there is a great degree of the comparative advantage and that there is growth in IIT for several product groups. Alam and Ahmed (2017) empirically investigated India's trade relations with the Gulf Cooperation Council (GCC) from 2001 to 2014. The analysis was carried out at the HS 2-digit level using various trade indices.…”
Section: India's Trade Relations With Australiamentioning
confidence: 99%
“…Sahib and Kari (2012) stress the important role of Saudi Arabia in terms of regional trade but find that economic integration with non‐GCC countries has been stronger in the last few years than among GCC members. Hence, GCC states have mainly looked for their trade partners outside of the Gulf region, in an effort to improve economic growth outcomes (Akhtar & Rouis, 2010; Alam & Ahmed, 2017).…”
Section: Underlying Determinants Of Gcc Trade Patternsmentioning
confidence: 99%
“…Another driving force behind GCC trading patterns (particularly Asian exports to the region) has been the strong immigration flows from South East Asia (Karayil, 2016). Hence, trade relations with countries like India and the Philippines are strengthening (Alam & Ahmed, 2017).…”
Section: Underlying Determinants Of Gcc Trade Patternsmentioning
confidence: 99%